A rare adverse effects of COVID-19 vaccine in a patient with a latent tumor: A case report and literature review - Xu, Wenjing; Nian, Weiqi (Frontiers in Oncology, 2023)
The 2019 novel coronavirus infection has done significant damage to the world. The effectiveness and safety of the vaccine, the most critical measure to control the epidemic, has attracted attention. In this case, we report the diagnosis and treatment of a rare patient with adverse effects of the COVID-19 vaccine who had G6PD deficiency by genetic tests. We discuss the possible impact of G6PD deficiency on COVID-19 infection and potential vaccine adverse effects. Patients with severe G6PD deficiency should be monitored for vaccine safety. This article may complement a rare mechanism of vaccine side effects and chemotherapy-related side effects.